Psychometric Properties of the German Version of the Young Positive Schema Questionnaire (YPSQ) in the General Population and Psychiatric Patients. Issue 4 (4th July 2022) - Paetsch, Andreas; Moultrie, Josefine; Kappelmann, Nils; Fietz, Julia; Bernstein, David P.; Kopf-Beck, Johannes
Abstract: Early adaptive schemas (EAS) are resilience-oriented counterparts to early maladaptive schemas (EMS), which are central in schema therapy. The Young Positive Schema Questionnaire (YPSQ) was developed as a measure of EAS but has been evaluated neither in relation to a clinical population nor in a German-speaking sample. Objectives of this study were therefore the psychometric validation of a German YPSQ in a community sample and the comparison of EAS to psychiatric patients. Participants were 1, 418 individuals from a community sample and 182 psychiatric patients with a main diagnosis of major depressive disorder. A factor structure of 10 EAS, instead of the original 14, demonstrated satisfactory factorial validity and internal consistency in both samples. EAS exhibited divergent validity to EMS, childhood trauma, and psychopathology. Convergent validity was evident with resilience, self-efficacy, and satisfaction with life. Support for incremental validity beyond EMS was especially shown for resilience, self-efficacy, and satisfaction with life, and was also evident for several dimensions of psychopathology. Individuals in the community sample exhibited more pronounced EAS compared to psychiatric patients with the exception of empathic consideration. Especially for concepts associated with mental health, the YPSQ has the potential to be a highly valuable addition to current research and practice.